A Systematic Review of Charcot Neuroarthropathy Misdiagnosis. Issue 1 (January 2022) - Safavi, Kiya Shazadeh; Torian, Joseph S.; Jimoh, Raliat O.; Jupiter, Daniel
Category: Diabetes; Other Introduction/Purpose: Charcot neuroarthropathy (CN) is a disabling condition of the foot and ankle with a prevalence of up to 13% of patients with Diabetes Mellitus (DM). In the acute phase, CN presents as a hot, swollen foot, with mild destruction of bone and joint structure. If left untreated it can progress to a chronic stage, with bone and joint destruction, presenting with a classic rocker bottom foot deformity. CN is often misdiagnosed in its acute phase; as a result the diagnosis is usually made once CN has progressed to the chronic phase. This delay causes prolonged treatment regimens and poorer outcomes. This systematic review examines the misdiagnosis of CN and the timeline preceding a correct diagnosis. Methods: A review of the literature was performed by searching Ovid Medline, CINAHL, and Scopus for articles published within the last five years that contained the terms Charcot and misdiagnosed, antibiotics, deep vein thrombosis, or osteomyelitis. The database search produced 110 articles, once duplicates were removed. 49 articles were screened out by title and 18 were screened by abstract; leaving 43 eligible articles. During the review of the 43 articles an additional 41 articles were added from references because they provided relevant information. Time of symptom onset to diagnosis was calculated in days, with 30 days counting as one month. Results: In total, 230 patients were included in analysis; of these, 27 (12%) presented with bilateral CN for a total of 257 affected extremities. Type 1 DM was present in 112/210 (53%) of patients, Type 2 DM in 98/210 (47%) of patients, and an unreported DM status in 20/230 (9%) patients. The average time from symptom onset to final diagnosis of CN was 84.8 days, with a range of 25 days to 203 days. Nearly half (110/230; 48%) of the patients experienced CN misdiagnosis. Of these, 99 specific misdiagnoses were reported, with the most common including cellulitis (22/99; 22%), fracture/sprain (18/99; 18%), deep vein thrombosis (13/99; 13%), osteomyelitis (11/99; 11%), and erysipelas and gout (10/99; 10%) each. A total of 42/146 (29%) of patients could recall an incidence of trauma prior to the onset of CN. Conclusion: A diagnosis of CN should be considered in patients with DM who present with peripheral neuropathy coupled with foot swelling, deformity, ulceration, or difficulty ambulating. This literature review has identified that nearly half of patients with CN are misdiagnosed, and many continue to ambulate and do not receive necessary total contact casting until they are correctly diagnosed later on. Subsequently, awareness of CN and the frequency of misdiagnoses associated with it is critical to preventing treatment delay. Further research is necessary to better clarify why CN is so frequently misdiagnosed and the amount of harm that can result from misdiagnoses.